2020
DOI: 10.5194/hess-24-2141-2020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the factors governing the ability to predict late-spring flooding in cold-region mountain basins

Abstract: Abstract. From 19 to 22 June 2013, intense rainfall and concurrent snowmelt led to devastating floods in the Canadian Rockies, foothills and downstream areas of southern Alberta and southeastern British Columbia, Canada. Such an event is typical of late-spring floods in cold-region mountain headwater, combining intense precipitation with rapid melting of late-lying snowpack, and represents a challenge for hydrological forecasting systems. This study investigated the factors governing the ability to predict suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 91 publications
0
28
0
Order By: Relevance
“…The high Nash-Sutcliffe efficiency, E NS , is partly due to the fact that it is rather easy for the land model to capture the yearly cycle of the streamflow only with snow processes (see, e.g., Knoben et al, 2020, demonstrating this for the Kling-Gupta efficiency), while rapid subsurface water movement, such as macropore movement, is largely missing in the land models (Gharari et al, 2019). Therefore, more caution is needed for the calibration of land model parameters for flood forecasting (Vionnet et al, 2020) for the Bow region and all the nivo-glacial river systems in western Canada, McKenzie, Yukon, and Colombia River basins.…”
Section: Discussionmentioning
confidence: 99%
“…The high Nash-Sutcliffe efficiency, E NS , is partly due to the fact that it is rather easy for the land model to capture the yearly cycle of the streamflow only with snow processes (see, e.g., Knoben et al, 2020, demonstrating this for the Kling-Gupta efficiency), while rapid subsurface water movement, such as macropore movement, is largely missing in the land models (Gharari et al, 2019). Therefore, more caution is needed for the calibration of land model parameters for flood forecasting (Vionnet et al, 2020) for the Bow region and all the nivo-glacial river systems in western Canada, McKenzie, Yukon, and Colombia River basins.…”
Section: Discussionmentioning
confidence: 99%
“…I would suggest that is not correct. A few examples: Rasmussen, et al 2010;Ikeda, et al 2010;Bonekamp, et al, 2018;Vionnet, et al 2020 L93 L368 "Decreases in terrain resolution may lead. .…”
Section: Specific Points Followmentioning
confidence: 99%
“…The authors note that as the computational grid becomes more coarse, fine scale topography smooths out and thus impacts the surface energetics and subsequent SWE distributions. Certainly, this was to have been expected and especially the case with snow cover simulation in mountain terrain where smaller computational cells can better represent the heterogeneities in mass and energy (Dornes, et al, 2008;Schlögl, et al 2016;DeBeer, et al 2017;Vionnet, et al 2020). However, there is seemingly no consideration of any of the small-to medium-scale (i.e., the 50 m to 250 m length scales considered) processes that might be affected by the scale perturbations, and no mechanistic discussion thereof to put the results into context.…”
mentioning
confidence: 99%
“…The elevation of the continental divide varies from 1130 to over 3600 m a.s.l. Meteorological data over the continental divide remain sparse and predominantly lie in the valleys where sites are accessible by road and AC power is more readily available (Vionnet et al, 2020). There are even fewer stations at higher elevations, hence the paucity of meteorological data over high-elevation regions (Pepin et al, 2015;Hernández-Henríquez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several significant flooding events have recently impacted the eastern slopes of the Canadian Rockies such as in June 2002 (Szeto et al, 2011), June 2005 (Ou, 2008;Shook, 2016), and the recent major flooding in June 2013 (Pomeroy et al, 2016;Liu et al, 2016;Kochtubajda et al, 2016). Whitfield and Pomeroy (2016) showed that flooding due to rain-on-snow events occurred more frequently in the late 19th and early 20th centuries than it does in the more recent period.…”
Section: Introductionmentioning
confidence: 99%